The New Business Models in the Knowledge Economy: the strategic way to the value creation - Lopes, I. T.; Martins, M. R. O. (Proceedings of the 2nd International Conference on Intellectual Capital and Knowledge Management and Organisational Learning, 2005)
Over the last decade we have seen the emergence of an economy in which the digital component has become a constant presence in all areas of knowledge. In the digital world, characterised and dominated by a complex connectivity, value assumes a complex meaning, which is strongly distinct from that used in the traditional economy. There are new business concepts, new strategies based on innovation, new mechanisms to create value, and a new need – to build methodologies and metrics that can measure and reflect it.